An introduction to cloud databases a guide for administrators - Neu, Wendy; Vlasceanu, Vlad; Oram, Andrew; Alapati, Sam R. (O'Reilly Media, 2019)
Cloud deployments have not only changed the way companies run mission critical databases; they've also transformed the roles of many people in production. With this practical report, database and system administrators, IT managers, and DevOps engineers will learn the ins and outs of running databases in the cloud. You'll explore the types of databases available, the difference between standard database services versus cloud native databases, and key considerations when planning the migration of on-premises databases to the cloud. Authors Wendy Neu, Vlad Vlasceanu, Andy Oram, and Sam Alapati explain how high-performing, highly available cloud environments free DBAs to focus on their core competencies, such as designing databases and optimizing applications that rely on them, while cloud providers handle the organization's routine infrastructure needs. With this report, you'll learn: The pros and cons of options in the cloud, such as managed, self-managed, and cloud native How the cloud transforms a DBA's role, including the new tasks a DBA needs to learn when cloud vendors assume traditional administrative tasks Steps required for migrating your databases to the cloud, such as planning, data transfer, and optimization.